2021
DOI: 10.3389/fmicb.2021.711471
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare-Associated Infections-Related Bacteriome and Antimicrobial Resistance Profiling: Assessing Contamination Hotspots in a Developing Country Public Hospital

Abstract: Hospital-built environment colonization by healthcare-associated infections-related bacteria (HAIrB) and the interaction with their occupants have been studied to support more effective tools for HAI control. To investigate HAIrB dynamics and antimicrobial resistance (AMR) profile we carried out a 6-month surveillance program in a developing country public hospital, targeting patients, hospital environment, and healthcare workers, using culture-dependent and culture-independent 16S rRNA gene sequencing methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 51 publications
0
16
0
1
Order By: Relevance
“…Sereira et al carried out the “Healthcare-associated Infections Microbiome Project,” a surveillance program of 6-month targeting, among others, HCWs, collecting 216 samples from their hands, mobile phones, and protective clothing. Through their culture-dependent and culture-independent analyses, despite the high abundance of total bacteria in the protective clothing, they observed a similar distribution of the ESKAPE bacteria investigated on the different sources identifying these sites as possible hot spots for HAI-related bacteria transmission ( 50 ). As we have previously pointed out, in addition to ESKAPE bacteria, Clostridium difficile is another important HAI-related bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sereira et al carried out the “Healthcare-associated Infections Microbiome Project,” a surveillance program of 6-month targeting, among others, HCWs, collecting 216 samples from their hands, mobile phones, and protective clothing. Through their culture-dependent and culture-independent analyses, despite the high abundance of total bacteria in the protective clothing, they observed a similar distribution of the ESKAPE bacteria investigated on the different sources identifying these sites as possible hot spots for HAI-related bacteria transmission ( 50 ). As we have previously pointed out, in addition to ESKAPE bacteria, Clostridium difficile is another important HAI-related bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…A high abundance of HAI-related pathogens were detected on all types of samples, however, the highest amount of bacteria and the greatest differences in alpha and beta-diversity was associated with the rectum samples. Moreover, during their studies, they concluded that 50% of the patients did not present any HAIs during hospitalization, 43.9% had an HAI during the hospitalization, and 6.1% was colonized by HAI-related bacteria, highlighting that a longer hospitalization seems to result in an increased HAIs incidence and, thereby, in an increased HAI-related pathogens detection, especially for bacteria like Klebsiella pneumoniae, Enterobacteriaceae, Staphylococcus spp, and Acinetobacter baumannii ( 50 ). Always through samples collected from different patients' body sites, Cruz-López et al examined the colonization process and the possible ways of transmission of HAI-related pathogens, since patient colonization has been suggested as a risk factor in HAI development.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…K. pneumoniae have been found on surfaces in hospitals in Brazil 15 , 16 , Tunisia 17 , Russia 18 , China 19 and Ghana 20 . A. baumannii was found on surfaces in hospitals in Brazil 21 , Turkey 21 , and Saudi Arabia 22 and on the surfaces of medical devices in Iran 23 . It was also found on surfaces in buildings surrounding hospitals in the US 24 .…”
Section: Introductionmentioning
confidence: 99%
“…These organisms not only persist on surfaces for up to several months 17 but are commonly found in healthcare environments, especially in low- and middle-income countries. K. pneumoniae have been found on surfaces in hospitals in Brazil 16, 15 , Tunisia 17 , Russia 18 , China 19 and Ghana 20 A. baumannii was found on surfaces in hospitals in Brazil 21 , Turkey 21 , Saudi Arabia 22 and on the surfaces of medical devices in Iran 23 . It was also found on surfaces in buildings surrounding hospitals in the US 24 .…”
Section: Introductionmentioning
confidence: 99%